Efektivitas Peran Audit Internal Dalam Pencegahan Fraud - Hakim, Luqman Nul; Suryatimur, Kartika Pradana (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Fraud is still a problem in various sectors in Indonesia, both private and non-private companies, even though it is within the scope of government. The existence of an internal control system is not enough to help the company to fortify the organization from fraud. The purpose of this study is to determine the stages of implementing an effective internal audit for fraud prevention as well as matters that need to be considered by internal audit to improve the efficiency and effectiveness of internal audit for fraud prevention. The research method used is qualitative with a literature review approach because this approach can provide an overview for researchers related to the development of topics regarding the role of internal audit and prevention of fraud. Sources of data used in this study is secondary data. The results of this study are the stages that must be carried out by internal audit so that fraud prevention is the planning stage, testing stage and monitoring of follow-up audits. In order to improve the efficiency and effectiveness of the role of internal audit, the organization can make the internal audit department independent, have full support from top management, and have competent, professional resources with high integrity and loyalty.